Identifikasi Jenis Ikan Hasil Tangkapan Nelayan yang didaratkan di Pangkalan Pendaratan Ikan (PPI) Kota Dumai Provinsi Riau - Djunaidi Djunaidi; Perdana Putra Kelana; Tyas Dita Pramesthy; Muhammad Nur Arkham; Rangga Bayu Kusuma Haris; Sri Yenica Roza (Cenderawasih University, 2022)
The Dumai City Fish Landing Base (FLB) is functioned to land fish both from within and from outside the City of Dumai to meet local consumption and for export purposes, however the various types of fish caught have not been properly identified. This study aims to identify and identify the types of fish caught by fishermen who are landed at the Fish Landing Base in Dumai City. The method used in this research was a survey. The fish species obtained were identified morphologically based on similarities in characteristics with the Taxonomy and Fish Identification Key books. The results showed that there were 14 types of fish from 14 families. all identified fish are neither protected nor endangered animals.